2020
DOI: 10.4049/jimmunol.2000315
|View full text |Cite
|
Sign up to set email alerts
|

CCL17 in Inflammation and Pain

Abstract: It has been reported that a GM-CSF→CCL17 pathway, originally identified in vitro in macrophage lineage populations, is implicated in the control of inflammatory pain, as well as arthritic pain and disease. We explore, in this study and in various inflammation models, the cellular CCL17 expression and its GM-CSF dependence as well as the function of CCL17 in inflammation and pain. This study used models allowing the convenient cell isolation from Ccl17 E/+ reporter mice; it also exploited both CCL17-dependent a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 69 publications
(103 reference statements)
0
20
0
Order By: Relevance
“…Thus, MCPIP1 might regulate the GM-CSF/IRF4/CCL17 pathway [64]. The chemokine CCL17, which is involved in inflammation and pain, was found to be induced upon treatment of macrophages with GM-CSF via JMJD3-regulated IRF4 signaling [64,65]. Although CCL17 has been reported to drive a pro-fibrotic macrophage phenotype [66], the lack of GM-CSF or IRF4 can also alter macrophage polarization independent of CCL17 [67].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, MCPIP1 might regulate the GM-CSF/IRF4/CCL17 pathway [64]. The chemokine CCL17, which is involved in inflammation and pain, was found to be induced upon treatment of macrophages with GM-CSF via JMJD3-regulated IRF4 signaling [64,65]. Although CCL17 has been reported to drive a pro-fibrotic macrophage phenotype [66], the lack of GM-CSF or IRF4 can also alter macrophage polarization independent of CCL17 [67].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, CCR4 signaling via CCL-17 has emerged as an attractive option to treat immune-inflammatory conditions driven by GMCSF. 55 Since nearly all Tregs express and use CCR4 receptor 56 for homing into sites of inflammation, CCR4 receptor blockade while attenuating inflammation may impact homeostatic resolution mechanisms. In this regard, targeting of CCL17 blockade is likely to spare Treg function while modulating Th2 recruitment.…”
Section: Discussionmentioning
confidence: 99%
“…The role of CCR4 and its ligands CCL17 and CCL22 in allergic disease is well established, 42–48 with the drug discovery efforts focused heavily on receptor antagonism ether with small molecules or mAbs. In addition, CCR4 signaling via CCL‐17 has emerged as an attractive option to treat immune‐inflammatory conditions driven by GMCSF 55 . Since nearly all Tregs express and use CCR4 receptor 56 for homing into sites of inflammation, CCR4 receptor blockade while attenuating inflammation may impact homeostatic resolution mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that there might not be a simple linear sequence of cytokine production and activity, but instead perhaps multiple mediator loops contributing to arthritis pain development [ 22 ]. It was also reported that neuropeptides/neurotrophins, namely NGF, CGRP, and substance P, are required for GM-CSF- and CCL17-driven inflammatory pain [ 47 ]. These mediators have been linked elsewhere with IL-23 biology [ 27 33 ] and exploring their link with IL-23 in arthritis pain would be worthwhile.…”
Section: Il-23 and Arthritis Pain: Questions And Issuesmentioning
confidence: 99%